Analysis Of The Attachment-Aversion Model Of Consumer-Brand Relationships In A Different Cultural Background - Novik, Veranika; Pinto, Patrícia; Guerreiro, Manuela (Journal of Tourism, Sustainability and Well-being, 2017)
Originally the Attachment-Aversion model of consumer-brand relationships, elaborated by Park, Eisingerich & Park in 2013, was analyzed with the help of the sample of English speaking respondents, living in Great Britain and the USA, and focused on two brands: Manchester United Football Club and Apple iPhone. The present study tries to validate the model regarding other type of brand and in conditions of another cultural background. The focal brand for the study was chosen from a high-end beauty category (Chanel). For the purposes of this research, a questionnaire was designed and spread online within the target population: the current students and alumni of Belarusian universities that are Russian/speaking, fluent in English and had a class in branding. A total of 273 responses was analysed using structural equation modelling. The outcomes of the research have shown that the Attachment-Aversion model of consumer-brand relationships has not proven to be totally versatile, while applied in the conditions of the other cultural background as some of the relationships of the model have shown to be insignificant. The enticing determinant has no effect on brand attachment relationship and the enabling determinant has no effect on the brand prominence. The implications of the findings are discussed.